2017
DOI: 10.1002/job.2217
|View full text |Cite
|
Sign up to set email alerts
|

Recovery from work‐related effort: A meta‐analysis

Abstract: Summary This meta‐analytic study examines the antecedents and outcomes of four recovery experiences: psychological detachment, relaxation, mastery, and control. Using 299 effect sizes from 54 independent samples (N = 26,592), we extend theory by integrating recovery experiences into the challenge–hindrance framework, creating a more comprehensive understanding of how both after‐work recovery and work characteristics collectively relate to well‐being. The results of meta‐analytic path estimates indicate that ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

34
406
4
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 319 publications
(452 citation statements)
references
References 92 publications
(124 reference statements)
34
406
4
8
Order By: Relevance
“…Without detachment, the energy loss cycle continues as resources are not replenished during off-job time, suggesting an increase in exhaustion and a decrease in vigour in the long term. Two recent meta-analyses (Bennett et al, 2018;Wendsche & Lohmann-Haislah, 2017) and one review (Sonnentag & Fritz, 2015) showed that detachment is systematically associated with less exhaustion and more vigour and the relationship may be stronger with fatigue (including exhaustion) than vigour. To date, two longitudinal studies have shown that lack of psychological detachment from work predicted an increase in job exhaustion over the course of 1 year (Sianoja et al, 2018;Sonnentag et al, 2010).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Without detachment, the energy loss cycle continues as resources are not replenished during off-job time, suggesting an increase in exhaustion and a decrease in vigour in the long term. Two recent meta-analyses (Bennett et al, 2018;Wendsche & Lohmann-Haislah, 2017) and one review (Sonnentag & Fritz, 2015) showed that detachment is systematically associated with less exhaustion and more vigour and the relationship may be stronger with fatigue (including exhaustion) than vigour. To date, two longitudinal studies have shown that lack of psychological detachment from work predicted an increase in job exhaustion over the course of 1 year (Sianoja et al, 2018;Sonnentag et al, 2010).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…It has been consistently suggested that insufficient recovery from work, especially over extended periods of time, results in resource depletion and impairs employees’ well‐being (Cropley & Zijlstra, ; Geurts & Sonnentag, ; Sonnentag, Venz, & Casper, ). However, longitudinal evidence on these expected long‐term detrimental effects on employee well‐being is scarce, as the current knowledge base mainly consists of findings from cross‐sectional studies together with diary studies (see Bennett, Bakker, & Field, ; Wendsche & Lohmann‐Haislah, , for meta‐analyses). This is an important research gap; only longitudinal research encompassing prolonged time periods can provide appropriate information about the (lagged) associations between recovery and employee well‐being.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite considerable empirical support for the direct effects between demands, psychological detachment, and strain proposed by the SD model at the between‐persons level (see Bennett, Bakker, & Field, ; Wendsche & Lohmann‐Haislah, , for reviews), the number of studies that have specifically examined the proposed mediating effects of psychological detachment is still limited (Sonnentag & Fritz, ; Sonnentag, Kuttler, & Fritz, ). Moreover, there is only limited knowledge about the role of personal characteristics for the relations between job stressors, psychological detachment, and strain.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, challenge (e.g., workload, cognitive demands) and hindrance (e.g., job insecurity) demands have previously been related to high affective rumination, lower psychological detachment from work during off‐job time, and greater need for recovery (Höge, Sora, Weber, Peiró, & Caballer, ; Kinnunen, Mauno, & Siltaloppi, ; Kinnunen et al ., ). A recent meta‐analysis has shown that especially challenge demands relate to poor detachment from work during off‐job time (Bennett, Bakker, & Field, ), which may refer to affective rumination. Hence, the most likely response of an employee faced with high challenge job demands and high job insecurity is not to adequately detach from work, but to continue a mental connection to work, which may be associated with physiological activation (Sonnentag & Fritz, ) to some extent preventing psychophysiological recovery.…”
Section: Introductionmentioning
confidence: 99%